Financial Distress Prediction: Empirical Evidence From Indian Automobile Companies - Poornima, S.; M, Theivanayaki (Journal of Commerce and Trade, 2012)
Financial distress is of crucial importance in financial management especially in the case of competitive environment. Failure is not an impulsive outcome and it grows constantly in stages. A spontaneous protective effort could be accommodated if the company is anticipated to be proceeding in the direction of potential bankruptcy and this can help alleviate the financial distress to all investor and decrease the costs of bankruptcy. This study extends a failure prediction model for Indian Automobile companies. This study hopes to accommodate some important results relevant to authorities and stake holders. The capability to detect potential financial problems at a premature stage is absolutely essential because it helps to ensure business, financial, economic and political environment stability. The results show good performance with a highly correct categorization factuality rate of more than 90%. Eight ratios were determined significant out of 38 financial ratios utilized in this analysis to discriminate among failed and non- failed companies. The significant variables are Operating margin (%), Gross profit margin (%), Return on long term funds (%), Total debt/equity, Cash earnings retention ratio, Exports as percent of total sales, Import companies in raw material consumed, Bonus component in equity capital (%)